2012
DOI: 10.1007/s10734-012-9563-y
|View full text |Cite
|
Sign up to set email alerts
|

Why do tertiary education graduates regret their study program? A comparison between Spain and the Netherlands

Abstract: In this paper we investigate the determinants of regret of study program for tertiary education graduates in Spain and the Netherlands. These two countries differ in their educational system in terms of the tracking structure in their secondary education and the strength of their education-labor market linkages in tertiary education. Therefore, by comparing Spain and the Netherlands, we aim at learning about the consequences that the two educational systems might have on the regret of study program in tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…The results show that a well-designed degree programme, that is academically prestigious, allows flexibility to combine course and areas of specialization, is vocationally oriented and whose content and objectives are known to employers, and is seen as demanding, contributes to an increase in earnings (see the positive entry of these variables in Table 3, columns 3 and 4). This result is similar to the finding in Kucel and Vilalta-Bufí (2013).…”
Section: Monetary Returnssupporting
confidence: 92%
“…The results show that a well-designed degree programme, that is academically prestigious, allows flexibility to combine course and areas of specialization, is vocationally oriented and whose content and objectives are known to employers, and is seen as demanding, contributes to an increase in earnings (see the positive entry of these variables in Table 3, columns 3 and 4). This result is similar to the finding in Kucel and Vilalta-Bufí (2013).…”
Section: Monetary Returnssupporting
confidence: 92%
“…In many subjective specifications of horizontal mismatch, the respondent specifies the job requirements in terms of the attended field of education. For instance, Kucel and Vilalta‐Bufí () classified employees as horizontally matched if she or he reported that exclusively the own attended field or a related field was appropriate for the job, whilst employees were classified as horizontally mismatched when a completely different field or no particular field was most appropriate for the job. Other studies based their definition on the degree to which employees perceive a fit between their field degree and their current job.…”
Section: Resultsmentioning
confidence: 99%
“…Van de Werfhorst, ; Wolbers, ; Bender and Roche, ). Horizontal mismatch also increases the likelihood of experiencing programme regret which is associated with substantial costs (Borghans and Golsteyn, ; Kucel and Vilalta‐Bufì, ). From this perspective, horizontal mismatch may reveal that the process of skill formation and the allocation of skills on the labour market are sub‐optimal.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with previous findings (Kucel & Vilalta-Bufí, 2013), dissatisfaction with the occupational outcomes from initial degrees was the prime reason that individuals regretted their initial decision, and returned to study a change qualification. Their dissatisfaction stemmed from employment issues including limited availability of employment and consequently poor job security (Carless & Arnup, 2011), dislike of the work (Borghans & Golsteyn, 2007), work-related stress, and moral issues (Bergin & Jimmieson, 2015;Minten & Forsyth, 2014).…”
Section: Dissatisfaction With Occupational Outcomessupporting
confidence: 79%